materialization of the Social Assistance policy:: the biases of financial management - Azevedo, Darana Carvalho de (Argumentum, 2024)
This article aims to analyze the objective conditions for the materialization of the social assistance policy in Brazil, from the perspective of the financial management of social public resources, in the period from 2015 to 2021. The temporal extension of the analysis starts from the year before the publication of the “Novo Regime Tax” depicting the effects of the new fiscal policy of increasing social spending. To this end, it carries out a survey of budget data in the SIGA Brasil system (which allows monitoring of the execution of the Union’s budget), with correction of values ​​at prices of the Extended Consumer Price Index (IPCA) of the Brazilian Institute of Geography and Statistics (IBGE), December 2021. The research demonstrates a greater decrease in budgetary investments for social assistance services, which even compromises the execution of assistance benefits.